MONITORING TOOLS TO ASSESS VEGETATION SUCCESSIONAL REGRESSION AND PREDICT CATASTROPHIC SHIFTS AND DESERTIFICATION IN MEDITERRANEAN RANGELAND ECOSYSTEMS - ALADOS, C L; ELAICH, A; PAPANASTASIS, V P; OZBEK, H; Freitas, H (Desertification in the Mediterranean Region a Security Issue)
The relationship between grazing intensity and ecosystem performance is complex and can depend on the prevailing ecological conditions. Previous studies have revealed that, in traditional grazing ecosystems, grazing can reduce ecosystem diversity in poor soils, but increase diversity and productivity in rich ecosystems subject to moderate grazing pressure. We are interested in detecting long-term structural changes or drift in an ecosystem before it is too late to prevent irreversible degradation. We analyzed vegetation spatial patterns and complexities of four Mediterranean communities: Tihmadit Region (Middle Atlas, Morocco), Camiyayla (Namrum) Region (Taurus Mountain, Turkey), Sykia Region (south of the Sithonia Peninsula, Greece), and Cabo de Gata Nijar Natural Park, Spain. Grazing disturbance was most intense near shelter and water points, which lead to gradients in soil surface disruption, compaction, and changes in the composition and cover of perennial vegetation. Dense matorral was more resistant to species loss than were moderately dense and scattered matorral, and grassland. Information fractal dimension decreased as we moved from a dense matorral to a discontinuous matorral, and increased as we moved to a more scattered matorral and to a grassland, which resulted in two opposing processes (interaction declining with ecosystem development, and immigration increasing with degradation) in a common pattern, i.e., small patches homogeneously distributed in the landscape. Characteristic species of the natural vegetation declined in frequency and organization in response to higher grazing disturbance, while species of disturbed areas exhibited the opposite trend. Overall, the spatial organization of the characteristic plants of each community decreased with increasing vegetation degradation, with the intensity of the trend being related to the species’ sensitivity to grazing. Developmental instability analyses of key species were used to determine the sensitivity of dominant key species to grazing pressure. Palatable species, which are better adapted to being eaten, such as Periploca laevigata, Phillyrea latifolia and Genista pseudopilosa, were able to resist moderate grazing pressure, while species of disturbed, grazed sites did not change developmental instability in response to increasing grazing pressure, such as Thymus hyemalis, Teucrium lusitanicum and Cistus monspeliensis. The usefulness of these monitoring tools in preventing land degradation is discussed.
Keywords: disturbance; grassland; Grazing; matorral (voyant); Mediterranean ecosystems; Spatial pattern; Vegetation

Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Scale-dependent segregation of seeders and resprouters in cork oak (Quercus suber) forests. - Coca, M.; Pausas, J. G. (Oecologia, 2012)
Recent studies showed that disturbances and water availability determine the richness among plants with different post-fire strategies of Mediterranean-type ecosystems. The aim of this study was to determine whether or not the scale of analysis has an influence on the effects of these factors and, therefore, on the segregation of the dominant post-fire strategies, obligate seeders and obligate resprouters, and facultative species. We recorded all woody species and geographical features on 94 (75 m(2)) plots of cork oak woodlands in the southern Iberian Peninsula. For each regenerative type (resprouters, seeders and species with both traits--facultative species), we tested the relationship between the number of species and the predictors using a generalised linear mixed model. The fixed predictor considered at the large scale was altitude, and fixed predictors considered at the local scale were aspect (north/south) and disturbance (fire and clearing by heavy machinery; yes/no). The random predictor was the factor of site. When this factor did not have significant effect for some regenerative types, these relationships was tested using a generalised linear model. Resprouting species were most represented at lower altitudes and in undisturbed sites, while seeders were also at lower altitudes but mostly on south-facing slopes, especially south-facing disturbed sites. For facultative species, site is the most important variable. The proportion of seeders from the total species is not related to altitude, but it is related to disturbance and aspect. These results suggest that there is no segregation of the richness of seeders and resprouters at the large scale (altitudinal gradient). Differences appeared at the local scale (aspect and disturbance).
The following values have no corresponding Zotero field: accession-num: 21863245
Keywords: Cork oak forests; disturbance; Mediterranean vegetation; Moisture regime; Post-fire strategies

Plant response to disturbance in a Mediterranean grassland: How many functional groups? - Lavorel, S; McIntyre, S; Grigulis, K (Journal of Vegetation Science, 2009)
. Data referring to changes in vegetation composition resulting from cattle exclosure and ploughing in a Portuguese pasture dominated by annuals were used to test hypotheses regarding the biology of species favoured or eliminated by disturbance in semi-natural herbaceous communities. These hypotheses were tested in two ways. First we compared the distribution of six a priori groups – grasses, small rosettes, large rosettes, small species with leafy stems, large species with leafy stems, legumes – across grazed, ploughed and undisturbed plots. In a second set of analyses we examined changes in the frequencies of individual biological attributes in response to grazing and ploughing. These analyses were carried out separately for grasses and dicot forbs. Overall, the species composition showed little response to either grazing or ploughing, though species dominance changed. This lack of responsiveness of species composition was attributed to the long history of intensive land use which has resulted in the loss of disturbance-intolerant species over entire landscapes. When considering a priori groups, small rosettes were indifferent to disturbance. grazing and ploughing showed that dominated. Large rosettes, large species with leafy stems and legumes were generally intolerant to both grazing and ploughing, though individual species may increase in response to disturbance. Small species with leafy stems were the only group favoured by grazing whereas ploughing favoured grasses. As to individual traits, grazing excluded large grass species with heavy seeds and promoted a flat rosette canopy structure and a small size, along with a moderate dormancy and protected inflorescences. In forbs, grazing favoured small species, as expected, while it excluded tall species, and, in contrast to earlier results, a rosette canopy. These attributes were consistent with responses of the a priori groups, though it would not have been possible to reconstruct groups directly from the attribute list. Ploughing had no effect on any of the forb traits. As to grass traits, flat- and short-statured species increased and heavy-seeded species decreased. Our analysis revealed two advantages of establishing plant functional classifications within life forms. Subgroups within forbs had contrasting types of behaviour. For the same trait patterns could differ within the grass group from within the forb group. Finally, this analysis emphasizes the need for plant functional classifications aiming at the identification of syndromes of co-occurring attributes rather than of lists of isolated traits of which actual combinations are not specified.
Keywords: Annual; disturbance; Grazing; Plant functional type; Ploughing; Portugal

Regeneration traits are structuring phylogenetic diversity in cork oak ( Quercus suber ) woodlands - Coca, Manuel; Pausas, Juli G. (Journal of Vegetation Science, 2009)
Keywords: Biodiversity; disturbance; logenetic community structure; phy-; phylodiversity; resprouters; seeders

Regeneration traits are structuring phylogenetic diversity in cork oak ( Quercus suber ) woodlands - Coca, Manuel; Pausas, Juli G. (Journal of Vegetation Science, 2009)
Keywords: Biodiversity; disturbance; logenetic community structure; phy-; phylodiversity; resprouters; seeders

Mediterranean vegetation dynamics: modelling problems and functional types - Pausas, J G (Plant Ecology, 1999)
Gap models have been applied to a wide range of ecosystems, mainly temperate and boreal forests, but rarely have such models been applied to Mediterranean ecosystems. In the present review we address some problems of gap models for predicting the long-term dynamics of Mediterranean ecosystems, and we suggest plant functional types suitable for modelling based on responses to disturbance. Most gap models do not take into account different life forms, interactions with ﬁre (e.g., resprouting and stimulation of the germination), and underground structures. Long term human impact on Mediterranean ecosystems has made a signiﬁcant impact on the current landscapes. That intense land use, involving long-lived slow-growing species, has had long-term consequences. It is not possible to understand Mediterranean vegetation and to validate any model without considering these factors. The lack of data for Mediterranean species may be overcome by taking into account correlations of traits and trade-offs between different functional types. A simple disturbance-based functional group system is discussed.
Keywords: disturbance; Fire ecology; gap models; Mediterranean; resprouting

Mediterranean vegetation dynamics: modelling problems and functional types - Pausas, J. G. (Plant Ecology, 1999)
Gap models have been applied to a wide range of ecosystems, mainly temperate and boreal forests, but rarely have such models been applied to Mediterranean ecosystems. In the present review we address some problems of gap models for predicting the long-term dynamics of Mediterranean ecosystems, and we suggest plant functional types suitable for modelling based on responses to disturbance. Most gap models do not take into account different life forms, interactions with ﬁre (e.g., resprouting and stimulation of the germination), and underground structures. Long term human impact on Mediterranean ecosystems has made a signiﬁcant impact on the current landscapes. That intense land use, involving long-lived slow-growing species, has had long-term consequences. It is not possible to understand Mediterranean vegetation and to validate any model without considering these factors. The lack of data for Mediterranean species may be overcome by taking into account correlations of traits and trade-offs between different functional types. A simple disturbance-based functional group system is discussed.
Keywords: disturbance; Fire ecology; gap models; Mediterranean; resprouting

Resprouting of Quercus suber in NE Spain after fire - Pausas, J G (Journal of Vegetation Science, 1997)
Many Mediterranean species have evolved strategies that allow them to survive periodic wildfires. Quercus suber trees resprout after fire, some from stem buds and others from basal buds only. In the former case the canopy recovers quickly. In the latter case the stem dies but the tree survives and regrows from basal sprouts. The probability of stem death and the degree of height recovery were studied after a fire in a Q. suber forest in NE Spain using logistic regression analysis. The results suggest that most trees survive after fire; the probability of stem death is negatively related to tree diameter; and recovery is positively related to tree diameter and to bark thickness. Implication for management and conservation of cork-oak forests are discussed.
Keywords: Cork oak; disturbance; Mediterranean; sprouting

LAS BOÑIGAS DE VACA, EL ENCESPEDADO DE POA BULBOSA, Y LA DIVERSIDAD EN UN PASTIZAL DE DEHESA - Malo, J E Juan E; Suarez, F; Vaca, L A S Boñigas D E; Poa, E L Encespedado D E; Diversidad, Y L A; Un, E N; Dehesa, Pastizal D E (Pastos, 1996)
The interactions of cattle dung pats, the Poa bulbosa Turf and the number of species in a pasture is analyzed at a 10x10 cm scale, through a four-year monitoring of 50 dung pats. Dung pats elimínate the Poa bulbosa Turf, and its recovering takes more than four years. The rest of the species are also displaced by dung pats, but they colonize the gaps much faster. Thus, the number of species by sample is significantly smaller on dung pats the first year after deposition (5-4 vs. 10-8), not distinguishable the second and third years (9-2 vs. 10-0 and 9-3 vs. 8-0), and significantly higher the fourth year after depo- sition (13-8 vs. 10-7). These results seem to be associated to the competitive behaviour of Poa bulbosa. This species colonizes the gaps slowly, but it is able to displace other species from them. The effect of the process is relatively small for the whole pasture due to the small área covered by dung pats. However, due to the uneveness of dung deposi- tion it can contribute to the development of pasture gradients of composition and diver- sity associated to grazing.
Keywords: Central Spain; centro de españa; competencia; competition; dinámica de pastizales; disturbance; dung; excrementos; herbivores; herbívoros; pasture dynamics; perturbación

Variabilité des nutriments foliaires de Quercus suber L dans différentes situations écologiques dans le massif des Maures (Var, France), et relations avec la production de liège - Orgeas, J; Bonin, G (Ann. For. Sci., 1996)
Variability of foliar nutrient contents of Quercus suber L in several ecological conditions in the Maures Mountains (Var, France), and relations with cork production. A monitoring of foliar nutrients has been undertaken on cork-oaks (Quercus suber L), in the Maures Mountains (Var, France). Simultaneously, the thickness of cork age rings has been studied to define the relationship of the cork production to nutrient contents under different ecological conditions. Foliar concentrations of ions evolved according to the season, the degradation state and the xericity of plots. Nitrogen appeared proportional to the physiological activity of the leaf, while calcium and potassium were stocked gradually. The calcium-magnesium antagonism was confirmed. Furthermore, changes of the nutrient concentrations in the undergrowth-clearing sites are reduced from the spring resumption of the metabolism. The growth of primary cork is linear with time, irrespective of year, climatic conditions and perturbations. The secondary (or reproductive) cork production is not linear with time and the age of trees, but it remains much higher than the primary cork production. The higher secondary cork productions are linked to the high contents of potassium and nitrogen, and to the moist and weakly disturbed plots. Magnesium is linked to small width thicknesses of cork age rings. Sodium and calcium do not appear to influence this cork production.
Keywords: Cork Production; disturbance; ecological conditions; foliar nutrients; Quercus Suber L